ナンキョク ドライバレー チイキ ノ エンコ ノ ミズ ノ サンソ ドウイタイ ソセイ ニツイテ - 加藤, 喜久雄; カトウ, キクオ; KATO, Kikuo (国立極地研究所, 1977)
P(論文) H_2O-CO_2酸素同位体交換平衡を用いた酸素同位体比の測定法は, ^<18>O/^<16>O濃度比を与えるものではなく,その活量比を与えるものである.その^<18>O/^<16>O活量比は,塩類溶液では測定温度により異なる.南極ドライバレー地域の塩湖の水が,通常の測定に用いられる25℃での^<18>O/^<16>O活量比を示すのは特例であり,0℃以下での活量比を示すのが通常である.そこで,塩湖の水について0℃での活量比を求めた.そのために,0゜CにおけるH_2O-CO_2酸素同位体分別係数を測定した結果は,1.0459であった.この値を用いてドンファン池とポニー湖の水について0℃における^<18>O/^<16>O活量比を測定した.その結果,0℃における活量比は25℃における活量比とは異なり,その差異は塩類の種類により大きく違うことが明らかになった. The oxygen isotope ratio determined from CO_2 equilibrated isotopically with the water sample provides the oxygen isotope activity ratio of the water sample. The solution of certain salts causes the oxygen isotope activity ratio to differ from the concentration ratio of the water sample. These effects are expected to increase with decreasing temperature. The oxygen isotope ratio is usually determined from CO_2 equilibrated at 25 ℃ with water. The salt water in the Dry Valleys, Antarctica is not assumed to register the oxygen isotope ratio determined at 25 ℃. So, the oxygen isotope ratio of the salt water was determined at 0℃. The CO_2-H_2O isotope fractionation factor determined at 0℃ is 1.0459. Using this value, the oxygen isotope ratio of salt water of Don Juan Pond and Lake Bonney at 0℃ was determined. The oxygen isotope ratio at 0℃ is fairly different from that at 25℃ and the difference varies greatly according to the kind of salt. departmental bulletin paper